Ética nas relações contratuais contemporâneas segundo pensamento de Amartya Sen : os requisitos da capacidade, boa-fé, autonomia e equidade nos contratos de massa - Modena, Maura Regina (My University, 2018)
The present research seeks to analyze, from the ethical point of view, contemporary contractual relations. This paper begins with the study of the institute of contracts, tracing a timeline from the origin of the contract in the Roman Law to the Modern times. Concerning this beginning among the Romans, the main point of interest for the purposes pursued in this dissertation was the way in which the issue of the capacity of the contracting parties was then dealt with. Afterwards, in the medieval period, the idea that seemed to us most relevant to the history of contract theory was the introduction of the principle of good faith. In the modern period, the outstanding contribution was the consecration of autonomy of will as a dogma. Thereafter, the research seeks to demonstrate the decline of the consecrated contractual forms established in the Classic Contractual Law, for with the emergence of the new mass consumer society and the corresponding immense increase of social and economic needs in the distribution of goods and services, it was no longer possible that contractual relations were based on individual will, at least not in the strict and classical sense of the term, since there was no longer a way to reconcile the full concept of expression of individual will, which presupposes the full cognitive domain of the contracting object, to the reality of the new patterns of social interaction created by the contemporary economy. In this scope, the research sought to demonstrate how they are uniformly accepted by the countless number of adherents who compose the other parts, these then homogenized by multiple standardized forms of adhesion, among them, the most recent ones, through computerized technology. The paper intends to develop an ethical reflection about the large-scale forms of contracting , which are done through these instruments of adhesion, increasingly complex in their form an technique, in which the State, although not sufficiently, protects the individual, acknowledging them as vulnerable in these contracts. It is aimed to understand the concept of capacity in the present times, as well as the limits in which the individual exercises his freedom of choice and autonomy in these acts. The research intends to demonstrate that the principle of good faith is no longer a "standard" of business relations in contemporary contracting, since the great majority of current contracts do not contemplate the real interest of the vulnerable party. Finally, the present paper tries to demonstrate the partial and, therefore, insufficient character of the measures taken to solve this difficulty through the laws and codes that regulate and that, in in most cases, bring “ex post” mitigations. The paper also attempts to suggest new solutions in order to protect the individual when contracting, as the legal requirement of simpler contractual instruments or as the facilitation in the agreement of rescission. Only in this way, we believe, it will be possible to achieve true equity in contractual relations, relations based on good faith and which promote the real interests of the parties, persuing a fairer and more balanced society.
A presente pesquisa busca analisar sob o ponto de vista ético as relações contratuais contemporâneas. Este trabalho inicia com o estudo do instituto do contrato, traçando uma linha de tempo desde a origem do contrato no Direito Romano até os tempos Modernos. Desse início entre os romanos interessou-nos para os fins perseguidos nesta Dissertação o modo como foi então tratada a questão da capacidade das partes contratantes. Na sequência, no período medieval a ideia que nos pareceu mais relevante para o esboço da história da teoria dos contratos foi a introdução do princípio da boa-fé. Já no período moderno a contribuição destacada foi a consagração do dogma da autonomia da vontade. Na sequência, a pesquisa procura demonstrar o declínio das formas de contratações consagradas no Direito Contratual Clássico, pois com o surgimento da nova sociedade de consumo massificada e o correspondente imenso incremento das necessidades sociais e econômicas de distribuição de bens e serviços, não foi mais possível que as contratações fossem baseadas na vontade individual, pelo menos não no sentido estrito e clássico da expressão, visto que não havia mais como compatibilizar o conceito pleno de manifestação da vontade individual, que pressupõe o domínio cognitivo pleno do objeto da contratação, com a realidade dos novos padrões de interação social criados pela economia contemporânea. Nesta linha, a pesquisa buscou demonstrar como são uniformemente aceitos pelo incontável número de aderentes que constituem as outras partes, homogeneizadas estas por múltiplas formas de adesão padronizadas, entre elas, as mais recentes, por meio da tecnologia informatizada. O trabalho pretende desenvolver uma reflexão ética sobre as formas de contratação em larga escala, feitas através desses instrumentos de adesão, cada vez mais complexos em sua forma e técnica, em que o Estado, embora insuficientemente, tutela o indivíduo, reconhecendo-o como vulnerável nessas contratações. Busca-se o entendimento do conceito de capacidade na atualidade, bem como dos limites em que o indivíduo exerce sua liberdade de escolha e autonomia nesses atos. A pesquisa busca demonstrar como nas contratações contemporâneas o princípio da boa-fé deixou de ser um “standard” das relações negociais, visto que a grande maioria dos contratos da atualidade não contempla o real interesse da parte vulnerável. Por fim, o presente trabalho tenta demonstrar o caráter parcial e, por isso, insuficiente das medidas tomadas para dar solução a essa dificuldade através das leis e códigos que regulam e que, na maioria das vezes, trazem mitigações “ex post”. O trabalho procura ainda sugerir novas soluções para que se proteja o indivíduo no momento de contratar como a exigência legal de instrumentos contratuais mais simples ou como a facilitação do distrato. Só assim, acreditamos, será possível conseguir verdadeira equidade nas relações contratuais, relações baseadas na boa-fé e que promovam os reais interesses das partes, buscando uma sociedade mais justa e equilibrada.
Keywords: Ética; Contratos; Direito - Filosofia; Ethics; Contracts; Law Philosophy